Μ-Raman spectroscopy of prehistoric paintings from the El Reno cave (Valdesotos, Guadalajara, Spain). (August 2017) - Iriarte, Mercedes; Hernanz, Antonio; Gavira-Vallejo, Jose M.; Alcolea-González, Javier; de Balbín-Behrmann, Rodrigo
Abstract: Prehistoric paintings from the El Reno cave, Guadalajara (Spain) have been studied by μ-Raman spectroscopy. Goethite (α-FeOOH) and haematite (α-Fe2 O3 ) have been used as pigments in this exceptional Palaeolithic site. Dolomite (CaMgCO3 ), anatase (TiO2 ), α-quartz (α-SiO2 ), hydromagnesite and the calcium carbonate (CaCO3 ) polymorphs calcite and aragonite have also been detected in the studied paint specimens. Clay minerals of the marl supporting the paintings could be the origin the significant spectral background of fluorescence radiation observed in the Raman spectra. The use of a pictorial recipe mixing haematite and amorphous carbon (charcoal or soot) to prepare the paint of a pictograph is proposed. Highlights: Palaeolithic rock paintings have been studied by μ-Raman spectroscopy. Goethite (α-FeOOH) and haematite (α-Fe2 O3 ) are the main pigments used. A pictorial recipe mixing haematite and amorphous carbon is proposed.